"Bali Becik" as a Supervision of Foreign Traveler Based on Local Culture - Bobby Briando; Budy Mulyawan; Wisnu Widayat; Sohirin; Arief Febrianto; Habbi Firlana; Pascalis Danny Kristi Wibowo; Muhammad Arief Adillah; Anida Sri Rahayu Mastur (International Journal of Religious and Cultural Studies, 2023)
This article aims to show that Local culture can be used as an alternative regulation in establishing a foreigner monitoring task force. The Foreigner Supervision Task Force "Bali Becik" is a unit formed by the Directorate General of Immigration based on the Local culture of the Balinese people. The Nusantara paradigm combined with the ability of artificial intelligence in viewing a phenomenon is the research method in this article. The results show that the "Bali Becik" Task Force is a task force formed based on the Local culture of Balinese culture which is part of the Nusantara paradigm. The value of the Local culture of "Bali Becik" which comes from the philosophy of Tri Hita Karana, which is the Balinese philosophy of harmony between humans, nature, and the gods. The task force aims to create a harmonious environment for both tourists and locals by cracking down on illegal activities and promoting responsible tourism